PEMBERIAN TEPUNG BAWANG PUTIH DAN TEPUNG JINTAN PADA PAKAN KOMERSIAL TERHADAP PERFORMA PUYUH (COTURNIX COTURNIX JAPONICA) PERIODE AWAL PRODUKSI - damayanti, febi; nur, Hanafi; Anggraeni, Anggraeni (Universitas Djuanda Bogor, 2018)
This research aims to improve the performance of the initial period of quail production and can provide information on the effects of each treatment of early period quail production performance. This research was carried out on February 7, 2017 up to March 15, 2017. This research was carried out on the Unit the entrepreneurial Cottage Farm Dewin Assalam SQF (Slamet Quail Farm) JL. Port II km. 20 Sukamantri Village Kec. Cikembar-Sukabumi West Java. This research using quail Coturnix coturnix laying Strain race japonica produced by CV. Slamet quail farm about 180 tail. Feed used is the feed sp2 with commercial treatment p0: the feed control commercial ( feed without additional flour garlic and flour caraway ), P1: the commercial feed with the addition of 2 % flour garlic P2: the commercial feed with additional % flour caraway 2, and P3: the feed ( feed commercial combination with the addition of 1 % flour garlic and 1 % flour caraway ). Treatment performed on quail 30 days until age 60 days.Feed and drinking water was given in adlibitum ( always available ).Design used is ral ( draft random complete ) to 4 treatment and 3 remedial.The results of the study showed the absence of influence on the consumption feed, conversion feed, the production of eggs and depleso.The results of the study showed that the feed commercial added flour caraway impact significant at rataan weight of eggs with the economic situation of 2 %.Keys : performances of quail , additional flour garlic and flour jintant , quail laying race , feed , cv slamet quail farm